The role of TCTEX1D4/PPP1 complex in cell proliferation and migration - Felgueiras, Juliana Carina Cardoso (2018)
Prostate cancer is one of the most prevalent and incident cancer in men, being a disquieting cause of men’s death worldwide. The widespread implementation of prostate-specific antigen (PSA) screening and the improvements on prostate cancer therapy have been leading to a markedly decrease in mortality. However, PSA use is controversial since it has been leading to the diagnosis and treatment of several prostate cancer cases that would not otherwise cause symptoms or threaten man’s life. Hence, the establishment of a panel of biomarkers and the discovery of new therapeutical targets for prostate cancer is a pressing need. Changes in several cell signaling pathways have been associated with de onset, development, and progression of prostate cancer. TGFβ signaling counterbalanced the mitogenic effects of androgens, thus being one of the most prominent pathways involved in controlling prostate growth. Mediators of TGFβ signaling pathway are strictly regulated by several mechanisms, among which reversible phosphorylation. This process involves a fine equilibrium between the action of protein kinases and phosphatases. PPP1 is a major serine/threonine phosphatase that regulates numerous cellular events, including TGFβ signaling. The majority of its functions are accomplished by association with regulatory subunits, known as PPP1-interacting proteins (PIPs). Recently, a novel PIP was found: TCTEX1D4, a dynein light chain protein that was already established as an interactor of TGFβ receptors. Its functions, nevertheless, remain poorly understood. This work identified TCTEX1D4 as an anti-proliferative agent in human prostate cells. Also, TCTEX1D4 activity seems to be regulated through binding to PPP1, as the disruption of TCTEX1D4/PPP1 complex resulted in enhancement of cell proliferation inhibition. Alternatively or in addition, TCTEX1D4 may indirectly regulate PPP1 function by modulating its subcellular localization. This complex doesn´t appear to play a major role in cell migration. Given the results, TCTEX1D4/PPP1 complex may constitute a potential target for the development of new prostate cancer therapies.